Pelatihan dan Peningkatan Kompetensi SDM Pengelola Homestay di Desa Tambong - Firda Rachma Amalia; Rudi Tri Handoko; Nurhalimah Nurhalimah; Auda Nuril Zazilah; Reni Nurjanah (Journal of Community Development, 2025)
Training and Competency Improvement Program for Homestay Managers in Tambong Village is a solution that can be offered to overcome the problem of low skills in the field of accommodation, especially front office and housekeeping, which can have an impact on the satisfaction of visiting tourists. Inadequate skills will also have an impact on the selling power of homestays. The majority of local residents only rent out houses without being equipped with the facilities and services needed by tourists. Tambong is one of the new tourist sites that is expected to become a mainstay of Banyuwangi and many tourists so that it is very necessary to include accommodation that includes the surrounding community, namely utilizing their homes as homestays that meet the standards. Therefore, with this, it is hoped that Banyuwangi State Polytechnic can participate in helping to solve partner problems with the capabilities possessed by the research team from Banyuwangi State Polytechnic. The solution chosen is training, competency certification and providing modules as well as full beds for rooms. The results of this service are certified competence in the field of front office and housekeeping and room settings that are suitable for homestays.